Impact of cardiorespiratory rehabilitation program on submaximal exercise capacity of Tunisian male patients with post-COVID19: A pilot study - Toulgui, Emna; Benzarti, Wafa; Rahmani, Chiraz; Aissa, Sana; Ghannouchi, Ines; Knaz, Asma; Sayhi, Amani; Sellami, Sana; Mahmoudi, Khaoula; Jemni, Sonia; Gargouri, Imene; Hayouni, Abdelaziz; et al. (Frontiers in Physiology, 2022)
Post-COVID19 patients suffer from persistent respiratory, cardiovascular, neurological, and musculoskeletal health complaints such as dyspnea, chest pain/discomfort, and fatigue. In Tunisia, the potential benefits of a cardiorespiratory rehabilitation program (CRRP) after COVID19 remain unclear. The main aim of this study was to evaluate the impact of a CRRP on submaximal exercise capacity, evaluated through the 6-min walk test (6MWT) data in post-COVID19 Tunisian patients. This was a cross-sectional study including 14 moderate to severe COVID19 patients aged from 50 to 70 years. CRRP was performed after the end of patients’ hospitalization in COVID19 units for extensive or severe extents of COVID19. Dyspnea (modified medical research council), spirometry data, handgrip strength values, 6MWT data, and 6-min walk work (i.e., 6-min walk distance x weight) were evaluated one-week pre-CRRP, and one-week post-CRRP. CRRP included 12 sessions [3 sessions (70 minutes each)/week for four weeks]. Exercise-training included aerobic cycle endurance, strength training, and educational sessions. Comparing pre- and post- CRRP results showed significant improvements in the means±standard deviations of dyspnea by 1.79±0.80 points (p<0.001), forced expiratory volume in one second by 110±180 ml (p=0.04), 6-min walk distance by 35±42 m (p=0.01), 6-min walk work by 2448±3925 mkg (p=0.048), resting heart-rate by 7±9 bpm (p=0.02) and resting diastolic blood pressure by 6±10 mmHg (p=0.045). In Tunisia, CRRP seems to improve the submaximal exercise capacity of post-COVID19 patients, mainly the 6-min walk distance and work.